The use of Google Translate on EFL students' language use in Writing and Attitudes - Delyana, Delyana; Tedjasuksmana, Hendra (Universitas Katolik Widya Mandala Surabaya, 2023)
This study explores students' attitudes towards GT, the impact of GT on their language use in writing, and the benefits and drawbacks associated with its uses. The research design employed a qualitative approach to gather data through writing tasks and questionnaires. The findings indicate that the use of GT did not significantly degrade the quality of language use in students' writing. The occurrence of spelling, word choice, and grammatical mistakes was minimal, demonstrating that GT had a positive impact on language acquisition and writing skills. Moreover, students showed positive attitudes towards GT, considering it beneficial for their writing and preferring it over other translation apps. The benefits of GT in writing included vocabulary expansion, time-saving, and increased confidence, while drawbacks included potential grammatical errors, incorrect translations, and dependency on the tool. Educators are recommended to promote responsible GT use and provide error corrective advice. More research on effective GT integration in writing lessons is recommended.